Pengaruh Pembiayaan Mudharabah Dan Pembiayaan Musyarakah Terhadap Profitabilitas Bank Umum Syariah: Studi Kasus Pada Bank BNI Syariah dan Bank Syariah Bukopin Periode 2015-2019 - Taqyudin, Yudin; Permatasari, Regita; Ariffin, Muhammad (Program Vokasi dan LPPM IBI Kesatuan, 2022)
Profitability is a measure of the success of a company or a bank. The higher the level of profitability of a bank, the survival of the bank will be more guaranteed. In this study profitability with the Return On Asset (ROA) indicator. In an effort to increase Sharia Commercial Bank Return On Assets (ROA) channeling working capital financing, namely mudharabah financing and musyarakah financing. The purpose of this study was to determine the effect of Mudharabah Financing and Musyarakah Financing on the Profitability (ROA) of Islamic Commercial Banks. This research was conducted using quarterly financial data at Bank BNI Syariah and Bank Syariah Bukopin 2015-2019 as samples. The results showed that mudharabah financing had a positive and significant effect on Return On Assets and Musyarakah Financing had a positive and significant effect on Return On Assets. Mudharabah financing and musyarakah financing simultaneously have a significant effect on return on assets. Keywords : Mudharabah Financing, Musyarakah Financing, Return On Asset